2015
DOI: 10.1016/j.clcc.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment, Outcomes, and Clinical Trial Participation in Elderly Patients With Metastatic Pancreas Adenocarcinoma

Abstract: Studies on the treatment patterns and outcomes of elderly patients with metastatic pancreas cancer remain limited. Therefore, an analysis of systemic therapy use, clinical trial participation, and outcomes in elderly patients with metastatic pancreas cancer was performed at our institution. Elderly patients who received systemic therapy had a longer survival compared with those who did not. However, therapeutic clinical trial participation was low and should be encouraged Background Pancreas adenocarcinoma ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…G. M. van der Geest et al Chemotherapy Use in Metastatic Pancreatic Cancer our nationwide study (≥75 years: median 4.0 months) was strikingly worse than the median of 7-8 months in previous mono-institutional cohorts of patients over 75 years of age [11,12]. Our observations are likely related to the nationwide character of our study with a less selective cohort of elderly patients.…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…G. M. van der Geest et al Chemotherapy Use in Metastatic Pancreatic Cancer our nationwide study (≥75 years: median 4.0 months) was strikingly worse than the median of 7-8 months in previous mono-institutional cohorts of patients over 75 years of age [11,12]. Our observations are likely related to the nationwide character of our study with a less selective cohort of elderly patients.…”
Section: Discussionmentioning
confidence: 34%
“…Most previous observational studies only included patients with microscopically confirmed pancreatic cancer [5,11,13,21,22,32]. Although pathologic confirmation of pancreatic cancer prior to chemotherapy is strongly recommended [27,33], one in ten of treated patients in our study started chemotherapy without prior microscopic tumor verification.…”
Section: Discussionmentioning
confidence: 93%
“…In our cohort, 72% of AG doses had to be reduced, but no patient was taken off chemotherapy due to intolerance despite having patients with ECOG PS up to 3 and ages up to 90. Historically, elderly and/or poor PS patients with PDAC, both of whom represent a clinically significant proportion of real-world patients outside of clinical trial populations, have been excluded from curative-intent strategies (13). Our data suggest that these patients may now have a possibility for potentially curative resection with the use of neoadjuvant AG.…”
Section: Discussionmentioning
confidence: 86%
“…curative tumor resection, there is an urgent demand for the development of novel and effective therapies of locally advanced and metastasized tumors. Besides primary liver cancer, the liver is also a frequent location for remote metastases of many tumor types including colorectal and pancreatic carcinoma occurring in the majority of the patients during the course of disease (De Groote and Prenen, 2015;Kotoyan et al, 2012;Li et al, 2015) which is currently still associated with a very poor survival prognosis unless resection or ablation as curative treatment modalities are feasible. Unfortunately, only the minority of patients are suitable candidates for curative treatment of primary and secondary liver tumors with the tumor liver burden considered as the major life-limiting cause in these patients (Bruix and Llovet, 2002;De Groote and Prenen, 2015;Forner et al, 2012;Jarzabek et al, 2011;Kotoyan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%